Dinamika Kesejahteraan Subjektif Juru Parkir di Banda Aceh - Muthia Maghfirah; Muhammad Rizki Akbar Pratama; Ida Fitria; Miftahul Jannah; Wilda Rahmi (State Islamic University (UIN) Ar-Raniry, 2018)
This study aims to identify subjective well being among parking officer around Banda Aceh. The current study also describing about the reason and feeling of being a parking officer. A descriptif qualitative approach has been done with depth interviews and code system data analysis. Participants of this study are 3 parking officer who are working in Banda Aceh. The results of study have shown that they have such a similar aspect of subjective well being, but also spesific condition for each of them. Those aspects including, positive emotions, negative emotion, and life satisfaction. This study has contributed the based line information regarding the description of subjective well being among parking officer in Banda Aceh.